Construção de módulos baseados em internet das coisas para coleta de dados e gerenciamento de informações - Solha, Matheus Coelho [UNESP] (2018)
Given the expansion of research and implementations in the Internet of Things area, several developers and scholars created tools that allowed the interpretation of the data generated by the environment around us and the availability of this information in an Internet network. With this technological advancement several devices were developed and improved the use of the Internet of Things concept, such as RaspberryPi and NodeMCU. Through the combination of microcontrollers, sensors and programming, a module based on this concept can be created, which allows better management of a particular environment or region. Based on these ideas, this project aimed at creating three modules capable of collecting data on temperature, humidity, luminosity and the opening of doors state, and then making them available on the Internet through the use of the Message Queuing Telemetry Transport (MQTT) protocol. Through the study of the most diverse electronic components, modular code planning for each sensor and development, we were able to construct the three low-cost modules, enabling a large scale development, allowing them to be used in many different areas.